On some integral inequalities for (h,m)-convex functions in a generalized framework - Kórus, P.; Nápoles Valdés, J.E. (Carpathian Mathematical Publications, 2023)
In this paper, we present some new integral inequalities of Hermite-Hadamard type. To obtain these results, general convex functions of various type are considered such as (h,m)-convex functions. The main results extend some previously known inequalities by taking fractional integral operators.